Evaluating the local food system of Manhattan, Kansas: producer and institution perspectives - Anegon, Angela K. (Kansas State University, 2014)
Agriculture is a driving industry for most areas of the United States, and the Great Plains region is no exception. In the state of Kansas, agriculture is the primary industry capturing a spot in the USDA 2012 Census of Agriculture’s Top 10 states for total agricultural sales, total crop sales, and total livestock sales (USDA, 2012). Despite the thriving agricultural industry, little research has been completed on the food systems supporting Kansas communities. What are the characteristics of a local food system within the fabric of an agriculturally rich state? The goal of this study was to evaluate the characteristics and perceptions of the local food system supporting Manhattan, Kansas – a metropolitan area located in North Central Kansas. Specifically, we wanted to understand producer barriers to expanding beyond direct markets into institutional markets such as school dining services, grocery stores, and hospital food services. The objectives were to 1) understand producer concerns for selling to institutions, 2) identify resources producers need to access institutional markets, 3) understand institutional preferences for local purchasing, and 4) understand producer and institution definitions of “local” food. In February 2013, a survey was mailed to 162 Kansas producers identified within a 150 mile distance of Manhattan, Kansas. The response rate was 63% and descriptive statistics were completed. Interviews were completed with eleven local institutions in March/April 2013. Common themes were qualitatively assessed. In general, farms were small-scale, producing a diversity of products, and utilizing direct-to-consumer markets while selling to institutions on a limited basis. Producer concerns for selling to institutions included low prices, small production quantities, and delivery costs. Institution concerns included product quantities, quality, and seasonality, quality of communication, and food safety. There was no consensus on a definition for “local” food systems. Opportunities for developing the local food system of Manhattan, Kansas include increasing seasonal production, increasing producer access to resources, and fostering relationships between local producers and institutions.
Keywords: Local food system; Direct-to-institution; Food system assessment; Agriculture, General (0473); Horticulture (0471)